SISTEM INFORMASI RAWAT JALAN PASIEN BPJS PADA RUMAH SAKIT - Fernando B Siahaan; Dede Awalludin (Jurnal Teknologi Informatika & Komputer, 2018)
Registration of outpatient BPJS at Rumah Sakit Islam Jakarta Pondok Kopi in its operational condition is obstacles that is a long time in the registration process due to the large volume of patient visit each day. So it takes a cient server based information system that can support so as to produce better service. The purpose of this study was to provide an alternative model of outpatient administration of BPJS patients. The method used in this study waterfall with stages analyze the needs of software, design, code generation, testing and support. The discussion by designing the system in the form of usecase diagrams, activity diagrams, sequence diagrams and ERD. The conclusion of this study computerized system made for RSIJPK can help overcome the problems in the process of registration of patients so that the time required to be faster. This electronic document is a â€œliveâ€ template. The various components of your paper [title, text, heads, etc.] are already defined on the style sheet, as illustrated by the portions given in this document.